THE EFFECT OF GOVERNMENT INVESTMENT AND SPENDING ON POVERTY IN INDONESIA - Said Munazir Al-Mahdali; Saharuddin Saharuddin (Journal of Malikussaleh Public Economics, 2023)
This study examines and analyzed  the effect of Investment and Government Expenditure on Poverty in Indonesia and uses secondary data from 2008 to 2020. The regression model used is a multiple linear regression model and classical methods. assumption test, which consists of a normality test, heteroscedasticity test, multicollinearity test. The regression tool used is Eviews 10. Based on the results of the study, it shows that investment has a negative and significant effect on the number of poor people in Indonesia, while government expenditure has an effect and is significant on the number of poor people in Indonesia and investment and government expenditure have an effect on the number of poor people in Indonesia. The test results for the coefficient of determination show that there is a relationship between the independent and dependent variables of 92.23%, and the remaining 7.77% is influenced by other variables outside this study.